Resilience during quarantine with the outbreak of COVID-19 in Iran - Yazdani, Shahram; Bayazidi, Maria; Afshari, Poorandokht (International Journal of Education and Cognitive Sciences, 2022)
Purpose of the review: The aim of this paper is to review Iran’s activities on resilience during home quarantine of outbreak of COVID-19 disease. Recent findings: Governmental activities were included; closing of all schools and universities, changes in office hours, closing shrines, delay in repayment of loans until three months, electricity and water costs were reduced for a month, and urging people not to visit each other, and do not take a trip during the Iranian new year. Also, the municipality and the Islamic Republic's army began to disinfect public passages. Medical activities: All medical staff and health providers provided care and treatment of patients in hospitals. Furthermore, midwives and other public health workers continued work in the health center. Also, physicians and other health workers such as midwives began setting up systems to answer questions from the public. Telephone counseling with women on any issues related to pregnancy, lactation, sex issues and other problems were provided by midwives. Staff of pharmacology schools started to prepare alcoholic sanitizer. Public activities were included; various groups of people have begun collecting public assistance to provide masks and disposable clothing for the health workers. Some groups started to disinfect the ATMs.